Intangibles disclosure and capital-raising in Australia : an analysis of information intensity - Abdul Halim Hazianti, Jaafar Hartini (N/A, 2012)
Intangibles disclosure and capital-raising in Australia : an analysis of information intensity by Abdul Halim Hazianti, Jaafar Hartini,